2016
DOI: 10.3389/fnins.2016.00585
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Local Information Indices Applied in Resting State Functional Brain Network Connectivity Prediction

Abstract: Anatomical distance has been widely used to predict functional connectivity because of the potential relationship between structural connectivity and functional connectivity. The basic implicit assumption of this method is “distance penalization.” But studies have shown that one-parameter model (anatomical distance) cannot account for the small-worldness, modularity, and degree distribution of normal human brain functional networks. Two local information indices–common neighbor (CN) and preferential attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Prior studies [20,21] considered anatomical distance as a major determinant of the connection between two ROIs (regions of interest) during network modelling. Studies showed that network topological factor, as well as the anatomical factor, have significant effects on network formation and performance [12,22,23]. It is generally confirmed that link prediction algorithms provide various rules for link establishment and network formation by quantifying the topological similarity between two unconnected nodes [24,25].…”
Section: Brain Network Modellingmentioning
confidence: 74%
See 3 more Smart Citations
“…Prior studies [20,21] considered anatomical distance as a major determinant of the connection between two ROIs (regions of interest) during network modelling. Studies showed that network topological factor, as well as the anatomical factor, have significant effects on network formation and performance [12,22,23]. It is generally confirmed that link prediction algorithms provide various rules for link establishment and network formation by quantifying the topological similarity between two unconnected nodes [24,25].…”
Section: Brain Network Modellingmentioning
confidence: 74%
“…If two nodes both have larger degrees, they score higher topological similarity and, therefore, their connecting probability is higher. At present, both network topological features and anatomical distance are treated as essential impact factors in modelling brain networks [12,22,23]. Vértes et al established a hemisphere-brain network by using an Economical Clustering Model (ECM) based on a link prediction algorithm of local topologies called common neighbours (CN) in order to simulate the formation mechanism of human brain networks [12,43].…”
Section: Generative Network Model Of Functional Brain Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The topological features selected have usually included global properties [11], local properties [12], community structures [13], and connections [14]. In recent years, researchers have proposed new methods for network feature analysis, which have been applied in brain disease machine learning research, such as hypergraph [15], high-order network [16], minimum spanning tree [17], and frequent subgraphs [18] methods. Brain network topological features provide a new perspective for combined research using fMRI and machine learning.…”
Section: Introductionmentioning
confidence: 99%